Associations between Financial Strength and Accounting Methods. - Injun, Supanee (Journal of Management Science Nakhon Pathom Rajabhat University, 2019)
This research studied the associations between accounting methods and financial strengths of the small and medium sized enterprises (SMEs) that registered in the Revenue Department’s ‘Single Set of Accounting Books’ Program in Nakhon Pathom Province. The researcher chose the research techniques to ensure that genuine data was provided, namely: the structured interview. The result of 342 structured interviews with the SMEs owners indicated that most of the SMEs adopted the methods that were easy to understand and to prepare. The financial strength of SMEs showed extremely different values. The statistical analysis at 0.05 level of confidence using Kruskal-Wallis H indicated these statistically significant associations: financial strength of liquidity had the most association with accounting methods, the firms using the average method of inventory valuation had higher financial strength than the firms using FiFo, the firms using the straight line method of depreciation calculation had higher financial strength than the firms using working-hour rate, the firms using the accrual basis for income realization had higher financial strength than the firms using the cash basis. The researcher suggested that the related government organizations should prepare an accounting computer application that provides choices for the right accounting methods that is opted for different types of SMEs to increases their financial strength and conformed to the regulations, not for only their convenience, and that a general employee of SMEs could do the data entry and financial report generating soon enough for the decision making of the owners. Suggestions for future research included the research that could improve the accounting computer application that provides right choices of accounting practices and more befitting to SMEs, and identify the direct effects of accounting methods on financial strengths. Article history : Received 18 May 2018 Revised 1 September 2018 Accepted 5 September 2018 SIMILARITY INDEX = 0.00